The influence of strength, speed, motor coordination and technique on the performance in crawl sprint - Hohmann, A.; Dierks, B.; Luehnenschloss, D.; Seidel, I.; Wichmann, E.
The performance in sprint swimming depends on different motor abilities. The structure of the performance in the 50 m crawl sprint is determined on a first level by two main factors: the swimming technique and coordination asto the sprint and pulling strength. Both factors are influenced on a second level by flexibility, anthropometric components, basic speed abilities and maximum strength resp. explosive power abilities. In total 134 male and female age-group and elite swimmers, who were between 10 and 19 years old, participated in the study. The performance in the 50 m crawl sprint varied from 25.0 s to 37.9 s within the male and 26.1 s to 40.2 s within the female swimmers. The investigation led to two different regression models of the structure of the swimming performance in the crawl sprint for male and female sprinters.